2021
DOI: 10.1590/fst.06420
|View full text |Cite
|
Sign up to set email alerts
|

Smart film of jackfruit seed starch as a potential indicator of fish freshness

Abstract: Smart film from jackfruit seeds containing anthocyanin extract has potential application as a freshness indicator of fish as they deteriorate, changing the color as a function of the product pH. The lower solubility percentage of the films was evidenced by the lower anthocyanin extract volume. The films presented mean water vapour permeability values of 3.034 g.mm/kPa.h.m 2 . The starch/anthocyanin film (ST4.0:AN5.0) showed higher tensile strength, while ST2.4:AN5.0 and ST3.0: AN5.3 showed lower resistance. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…Starch-based films also have the potential to be the polymer base for intelligent food packaging. For example, Vedove et al (2021) developed an intelligent packaging from cassava starch and anthocyanin, which acted as the natural pH indicator in meat stored at 6 • C. Costa et al (2021) also incorporated anthocyanin as a pH indicator in the film of jackfruit seed starch. The authors observed the potential as an intelligent packaging to indicate the freshness of fish, presenting a perceptible color variation in the films within 48 h (Costa et al, 2021).…”
Section: Starch-based Films: a Promising Materials For Food Packagingmentioning
confidence: 99%
“…Starch-based films also have the potential to be the polymer base for intelligent food packaging. For example, Vedove et al (2021) developed an intelligent packaging from cassava starch and anthocyanin, which acted as the natural pH indicator in meat stored at 6 • C. Costa et al (2021) also incorporated anthocyanin as a pH indicator in the film of jackfruit seed starch. The authors observed the potential as an intelligent packaging to indicate the freshness of fish, presenting a perceptible color variation in the films within 48 h (Costa et al, 2021).…”
Section: Starch-based Films: a Promising Materials For Food Packagingmentioning
confidence: 99%
“…Ademais, o uso de plastificantes, como glicerol, pode ser necessário para formação de uma matriz contínua e melhora das propriedades mecânicas, uma vez que interferem na ligação de hidrogênio (Acquavia et al, 2020;Maraveas, 2020) e na interação macromolecular durante o rearranjo da amilopectina ou amilose (Fu et al, 2018). O amido de diferentes fontes vegetais e seus resíduos foram explorados para a elaboração de filmes, tais como amido de mandioca (Luchese et al, 2021;Huang et al, 2020), de arroz (Suriyatem et al, 2018), de quinoa (Pagno et al, 2015), de milho (Luchese et al, 2019), de araruta (Nascimento et al, 2021;Nogueira et al, 2019), de batata (Balakrishnan et al, 2017), de semente de jaca (Costa et al, 2021), semente de manga (Silva et al, 2019), de polpa de banana (Pelissari et al, 2017) e de polpa de maçã (Tirado-Gallegos et al, 2018).…”
Section: Biopolímeros Extraídos De Resíduos Agroindustriais: Matéria-prima Para Elaboração De Filmesunclassified
“…The color change of anthocyanins incorporated within starch in the exposure of volatile amines including trimethylamine, dimethylamine, and ammonia during the deterioration of fish meat, which is in turn owing to the decomposition of amino acids and urea and subsequently increasing the pH of the media, was considered a possible sensing mechanism for visual monitoring of food freshness. According to the satisfactory results of the application of the fabricated smart films in fish and shrimp samples, the authors suggested using them as a food freshness label in the product packaging to visually monitor the food quality …”
Section: Optical (Bio)sensing Applications Of Phytochemicalsmentioning
confidence: 99%